Societal fragilities and resilience: The emergence of peoplehood in Belarus. Issue 2 (July 2021) - Petrova, Irina; Korosteleva, Elena
The article examines societal fragilities and local resilience strategies in Belarus with a particular focus on the notion of peoplehood . Premised on the idea of evolving forms of agency under the Anthropocene, and the emergent complexity-thinking in International Relations, the article draws on these approaches to societal fragilities and community resilience to understand and explain the unprecedented levels of mobilization occurring in Belarus since the disputed presidential election in August 2020. To this end, the article zooms onto the local communities to provide an analytical perspective on the study of resilience as self-organization . In line with complexity-thinking, it argues in favor of history-specific processual identities, shaped by the aspirations of a "good life, " and realized via local support infrastructures which lie at the heart of societal resilience in Belarus. Yet, the potential of all these elements to actualize into a sweeping transformative force, referred to as "peoplehood" in this article, is rare, and comes at a time of unprecedented crises and existential threats to the life of a community. The Belarusian society seems to be undergoing such a moment that not only makes it more resilient and adaptive to change; it also transforms it into a new form of societal being, self-aware of its worth, self-organized, and self-reliant on its inner capabilities to fight for a life of excellence. The article traces these moments of becoming with, and societal being, via a critical discussion of fragilities and the elements of resilience, actualized into peoplehood.